Damage and Loss Due to Ceratocystis fimbriata in Eucalyptus Wood for Charcoal Production - Fernandes, Bianca Vique; Vinha Zanuncio, Antonio Jose; Furtado, Edson Luiz [UNESP]; Andrade, Helder Bolognani (North Carolina State Univ Dept Wood & Paper Sci, 2014)
Eucalyptus plantation area has been increasing in Brazil, with 29% of the total plantation area being located in Minas Gerais state, which currently is being utilized primarily for charcoal production. However, diseases often increase the production costs of Eucalyptus. The objective of this study was to evaluate the effect of the fungus Ceratocystis fimbriata Ellis & Halsted on Eucalyptus wood for charcoal production. The basic density, volume, extractives, lignin, and holocellulose content of the wood were determined, as well as the gravimetric yield, volatile matter, fixed carbon, ash, and gross calorific values of charcoal. The introduction of the fungus C. fimbriata to Eucalyptus decreased the wood production and holocellulose content, but it also increased the wood's lignin and extractives content. The chemical changes in the wood did not affect the charcoal produced. Volume of wood losses due to C. fimbriata can result in a loss of up to 3478.43 US$/ha.
Keywords: Disease; Extractives; Gravimetric yield; Lignin